Method for forming SEI film on surface of silicon anode

By using pulse voltage treatment to form an SEI film on the surface of the silicon anode, the problem of difficult control of composition and thickness in the existing technology is solved, and efficient improvement of the electrochemical performance of the silicon anode and enhancement of interface stability are achieved.

CN120767279APending Publication Date: 2025-10-10NINGXIA UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510906279.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing technologies are unable to precisely control the composition and thickness of the SEI film when forming the silicon anode, resulting in severe irreversible capacity loss of the battery, and traditional methods may increase the risk of side reactions.

Method used

The SEI film is formed on the surface of the silicon anode by using the pulse voltage treatment method. By rationally designing the amplitude, time and duration of the pulse voltage, an SEI film with a specific composition ratio and microstructure is induced to form on the electrode surface.

Benefits of technology

It significantly improves the first coulombic efficiency of silicon anode, reduces irreversible capacity loss, enhances interface stability, simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767279A_ABST
    Figure CN120767279A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and particularly relates to a method for forming an SEI film on the surface of a silicon anode. The invention provides a technical scheme for forming SEI through pulse voltage driving customization, parameters such as pulse voltage amplitude, pulse voltage high and low potential duration time and pulse time are reasonably designed, an SEI film with a specific component proportion and a microstructure is induced to be formed on the surface of an electrode, the first coulombic efficiency of a silicon anode is remarkably improved, and the service life of the silicon anode is prolonged. The irreversible capacity loss is reduced, meanwhile, the interface stability is enhanced, and a brand new SEI regulation and control strategy is provided for the development of the high-energy-density lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a method for forming a SEI film on the surface of a silicon anode. Background Art

[0002] With the widespread application of lithium-ion batteries in new energy vehicles, portable electronic devices, and energy storage, further improving the energy density and cycle life of batteries has become a research hotspot. Silicon (Si) is considered to be one of the most promising negative electrode materials for the new generation of lithium-ion batteries due to its extremely high theoretical specific capacity (~4200mAh / g). However, the volume expansion rate of silicon materials can reach over 300% during the charge and discharge process, resulting in damage to the electrode structure, repeated rupture and recombination of the SEI film, and ultimately irreversible capacity loss, which seriously restricts the practical application of silicon anodes.

[0003] At present, the solutions for improving the electrochemical performance of silicon anodes mainly include nanostructure design, carbon-based composite material coating, electrolyte additive regulation and pre-lithiation technology. Among them, optimizing the structure and composition of SEI (solid electrolyte interphase membrane) is considered to be a key way to improve the first coulombic efficiency (ICE) and electrode interface stability. Existing technologies mostly use constant potential or constant current formation processes to slowly form the SEI film by controlling the electrode voltage. However, this method cannot accurately control the composition and thickness of SEI, which often leads to a thick SEI film and disordered structure, making it difficult to effectively suppress irreversible capacity loss. At the same time, the rapid formation of SEI film is promoted by increasing the formation temperature, but this method easily leads to an increase in SEI film thickness, reduces the first reversible capacity of the battery, and also has the risk of increased side reactions. Summary of the Invention

[0004] The object of the present invention is to provide a method for forming a SEI film on the surface of a silicon anode.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for forming an SEI film on the surface of a silicon anode, comprising the following steps:

[0007] Providing a device comprising a silicon anode, a counter electrode, and a lithium-ion battery electrolyte, wherein the silicon anode and the counter electrode are immersed in the lithium-ion battery electrolyte;

[0008] The device is subjected to a pulse voltage treatment to form a SEI film on the surface of the silicon anode.

[0009] Preferably, the conditions of the pulse voltage treatment include: pulse high potential is 0.7~1.2V, pulse high potential time is 1~30ms, pulse low potential is -0.5~0.1V, pulse low potential time is 1~30ms, and the duration of pulse voltage treatment is 1~60s.

[0010] Preferably, the conditions of the pulse voltage treatment include: a pulse high potential of 1.2 V, a pulse high potential time of 1 ms, a pulse low potential of 0.1 V, a pulse low potential time of 1 ms, and a duration of the pulse voltage treatment of 10 s.

[0011] Preferably, the conditions of the pulse voltage treatment include: a pulse high potential of 1.2 V, a pulse high potential time of 30 ms, a pulse low potential of 0.1 V, a pulse low potential time of 1 ms, and a duration of the pulse voltage treatment of 10 s.

[0012] Preferably, the conditions of the pulse voltage treatment include: a pulse high potential of 1.2 V, a pulse high potential time of 1 ms, a pulse low potential of 0.1 V, a pulse low potential time of 30 ms, and a duration of the pulse voltage treatment of 10 s.

[0013] Preferably, the silicon anode comprises a current collector and elemental silicon located on the surface of the current collector;

[0014] The thickness of the silicon anode is 30 to 50 μm, and the loading amount of the elemental silicon on the silicon anode is 0.6 to 1.8 mg / cm 2 ;

[0015] The current collector includes copper foil or foam copper; the thickness of the copper foil is 6 to 20 μm, and the thickness of the foam copper is 0.5 to 1.5 mm.

[0016] Preferably, the method for preparing the silicon anode comprises the following steps:

[0017] dispersing silicon nanoparticles in ethanol to obtain an ethanol suspension;

[0018] The ethanol suspension is drop-coated on a current collector, and then dried and pressed in sequence to obtain the silicon anode.

[0019] Preferably, the particle size of the silicon nanoparticles is 60 to 120 nm; the dosage ratio of the silicon nanoparticles to ethanol is 0.1 to 1 g: 8 to 12 mL;

[0020] The ratio of the ethanol suspension to the diameter of the current collector is 10-30 μL:1.2 cm;

[0021] The pressing pressure is 30-40 MPa and the pressing time is 30-60 s.

[0022] Preferably, the lithium-ion battery electrolyte includes LiPF6 electrolyte or LiTFSI electrolyte.

[0023] Preferably, the device is a lithium-ion half-cell; the counter electrode of the lithium-ion half-cell is a metallic lithium sheet.

[0024] The present invention provides a method for forming an SEI film on the surface of a silicon anode, comprising the following steps: providing a device containing a silicon anode, a counter electrode and a lithium ion battery electrolyte, wherein the silicon anode and the counter electrode are immersed in the lithium ion battery electrolyte; and subjecting the device to a pulse voltage treatment to form an SEI film on the surface of the silicon anode.

[0025] The present invention proposes a technical solution for customized SEI formation driven by pulse voltage. By rationally designing parameters such as the pulse voltage amplitude, the duration of high and low potentials of the pulse voltage, and the pulse time, an SEI film with a specific composition ratio and microstructure is induced to form on the electrode surface, which significantly improves the first coulombic efficiency of the silicon anode, reduces the irreversible capacity loss, and enhances the interface stability, providing a new SEI regulation strategy for the development of high-energy-density lithium-ion batteries.

[0026] The device provided by the present invention can be a lithium-ion half-cell. After the battery assembly is completed, the present invention applies a short high-frequency pulse voltage to the battery. The pulse voltage is intended to oscillate the directional distribution of anionic groups near the double layer on the electrode surface at high speed, so as to promote more anionic groups to come into contact with the electrode interface, thereby forming more inorganic SEI components derived from anions in the electrolyte. The process of applying a short pulse to a fresh battery can replace the formation step in the actual production process. Different pulse protocols are set by modulating the duration of the pulse high potential and low potential to form different SEI seed layers on the electrode surface. The SEI layer can continue to be formed through the subsequent constant current discharge process. Compared with traditional methods, the pulse voltage pretreatment method has the following advantages as a method for pre-forming SEI:

[0027] 1. Simple operation and cost saving:

[0028] The present invention performs a short pulse pretreatment on the assembled battery without any treatment of the silicon material itself. The effect is the same as the chemical formation process in actual production. The surface of the silicon anode is electrochemically pretreated by a short pulse voltage to promote the formation of a solid electrolyte interface (SEI) layer, improve the electrochemical performance of the silicon anode, and reduce the investment cost in the chemical formation process.

[0029] 2. The solid electrolyte interface can be customized:

[0030] When a pulse voltage is applied to the battery, the double layer potential near the electrode surface is affected by the intermittent changes in the high and low potentials of the pulse. The migration process of the anionic groups near the double layer is affected by two driving forces with different results, namely electromigration and diffusion potential. When the double layer potential changes, the competition between the two driving forces that drive the movement of anions can be changed. By setting different pulse protocols, different ionic groups can be screened to pass through the double layer, and the purpose of customizing the SEI components can be achieved. Through customized pulse voltage drive, a dense and stable SEI layer can be quickly formed on the electrode surface, optimizing the composition and structure of the SEI, effectively reducing irreversible capacity loss, and significantly improving the first coulombic efficiency of the silicon anode, while taking into account interface stability and cycle life.

[0031] 3. Universal applicability:

[0032] The present invention is achieved by oscillating the distribution state of ionic groups in the double electric layer near the electrode interface through a pulse voltage, and has universal applicability to conventional liquid lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 TEM overall morphology of SEI formed on the silicon anode of Example 1, HRTEM detailed morphology of SEI formed on the silicon anode, elemental analysis selected area morphology of SEI on the silicon anode surface, and element distribution diagram of SEI on the silicon anode surface;

[0034] Figure 2 XRD pattern and Raman pattern of the silicon anode of Example 1;

[0035] Figure 3 This is the XPS graph of the silicon anode of Example 1;

[0036] Figure 4 The EIS impedance analysis diagram of the battery of Example 1 before and after pulse treatment, the CV comparison curve of the silicon anode in the initial state and after pulse treatment, and the voltage-to-capacity curve of the silicon anode in the initial state and the first week after pulse treatment;

[0037] Figure 5 This is the XPS graph of the silicon anode of Example 2;

[0038] Figure 6 EIS impedance analysis diagram of the battery of Example 2 before and after pulse treatment, CV comparison curve of the silicon anode in the initial state and after pulse treatment, and voltage-to-capacity curve of the silicon anode in the initial state and the first week after pulse treatment;

[0039] Figure 7 This is the XPS graph of the silicon anode of Example 3;

[0040] Figure 8EIS impedance analysis diagram of the battery of Example 3 before and after pulse treatment, CV comparison curve diagram of the silicon anode in the initial state and after pulse treatment, and voltage-to-capacity curve diagram of the silicon anode in the initial state and the first week after pulse treatment;

[0041] Figure 9 A curve diagram of voltage and time during the pulse voltage treatment process provided by the present invention;

[0042] Figure 10 This is an EIS impedance analysis diagram of the battery of Comparative Example 1;

[0043] Figure 11 EIS impedance analysis diagram of the battery of Comparative Example 2

[0044] Figure 12 This is an EIS impedance analysis diagram of the battery of Example 4;

[0045] Figure 13 This is an EIS impedance analysis diagram of the battery of Example 5;

[0046] Figure 14 The EIS impedance analysis graph and TEM graph of the battery of Comparative Example 3;

[0047] Figure 15 This is the XPS graph of the silicon anode of Comparative Example 3;

[0048] Figure 16 The EIS impedance analysis graphs of the battery obtained by the three treatment methods in Test Example 1 and the TEM images of the silicon electrode after formation;

[0049] Figure 17 This is a high-resolution XPS image of the SEI on the surface of the PC sample of Test Example 1. DETAILED DESCRIPTION

[0050] The present invention provides a method for forming an SEI film on the surface of a silicon anode, comprising the following steps:

[0051] Providing a device comprising a silicon anode, a counter electrode, and a lithium-ion battery electrolyte, wherein the silicon anode and the counter electrode are immersed in the lithium-ion battery electrolyte;

[0052] The device is subjected to a pulse voltage treatment to form a SEI film on the surface of the silicon anode.

[0053] The present invention provides a device comprising a silicon anode, a counter electrode and a lithium ion battery electrolyte, wherein the silicon anode and the counter electrode are immersed in the lithium ion battery electrolyte.

[0054] In the present invention, the silicon anode preferably includes a current collector and elemental silicon located on the surface of the current collector; the thickness of the silicon anode is preferably 30 to 50 μm, and the loading amount of the elemental silicon on the silicon anode is preferably 0.6 to 1.8 mg / cm 2 ; The current collector preferably includes copper foil or foam copper; the thickness of the copper foil is preferably 6 to 20 μm, and the thickness of the foam copper is preferably 0.5 to 1.5 mm.

[0055] In the present invention, the method for preparing the silicon anode preferably comprises the following steps:

[0056] dispersing silicon nanoparticles in ethanol to obtain an ethanol suspension;

[0057] The ethanol suspension is drop-coated on a current collector, and then dried and pressed in sequence to obtain the silicon anode.

[0058] In the present invention, the silicon nanoparticles preferably have a particle size of 60 to 120 nm; the silicon nanoparticles are preferably purchased from MacLean Reagent Network; and the ratio of the silicon nanoparticles to ethanol is preferably 0.1 to 1 g: 8 to 12 mL. In the present invention, the dispersion is preferably performed under ultrasonic conditions, and the ultrasonication time is preferably 30 minutes.

[0059] In the present invention, the ratio of the volume of the ethanol suspension to the diameter of the current collector is preferably 10-30 μL:1.2 cm. The present invention does not specifically limit the drop coating process, and can be performed using a process well known to those skilled in the art. In a specific embodiment of the present invention, the drop coating process is as follows: the ethanol suspension is evenly applied to a 1.2 cm diameter foam copper current collector by drop coating three times.

[0060] In the present invention, the drying temperature is preferably 80°C and the drying time is preferably 5 hours. The drying can remove the residual solvent. In the present invention, the pressing pressure is preferably 30-40 MPa and the pressing time is preferably 30-60 seconds.

[0061] In the present invention, the lithium-ion battery electrolyte preferably comprises a LiPF6 electrolyte or a LiTFSI electrolyte. The concentration of the LiPF6 electrolyte is preferably 1 mol / L. The solvent of the LiPF6 electrolyte preferably comprises EC, DEC, and FEC. The volume ratio of EC to DEC is preferably 1:1. The mass percentage of FEC in the LiPF6 electrolyte is preferably 10%. The concentration of the LiTFSI electrolyte is preferably 1 mol / L. The solvent of the LiTFSI electrolyte is preferably THF or DME.

[0062] In the present invention, the device is preferably a lithium-ion half-cell; the lithium-ion half-cell is preferably a CR2032 button cell; the counter electrode of the lithium-ion half-cell is preferably a metal lithium sheet, and the diameter of the metal lithium sheet is preferably 16 mm. In the present invention, the CR2032 button cell also preferably includes a CR2032 battery case, a gasket, and a funnel spring; the gasket preferably has dimensions of 15.8 mm (diameter) by 1.0 mm (thickness); and the funnel spring preferably has dimensions of 15.4 mm (diameter) by 1.2 mm (thickness).

[0063] The present invention has no special limitation on the assembly process of the CR2032 button battery, and the process well known to those skilled in the art can be adopted.

[0064] After obtaining the device, the present invention performs pulse voltage treatment on the device to form a SEI film on the surface of the silicon anode.

[0065] In the present invention, the conditions of the pulse voltage treatment preferably include: pulse high potential of 0.7 to 1.2 V, pulse high potential time of 1 to 30 ms, pulse low potential of -0.5 to 0.1 V, pulse low potential time of 1 to 30 ms, and duration of the pulse voltage treatment of 1 to 60 s. In the present invention, the voltage and time curves during the pulse voltage treatment are as follows: Figure 9 shown.

[0066] In the present invention, the thickness of the SEI film formed on the surface of the silicon anode is preferably 7 to 12 nm.

[0067] In the present invention, the pulse voltage treatment method mainly utilizes the pulse voltage to oscillate the dynamic migration process of anion groups near the double layer on the surface of the silicon anode. Specifically: (1) When the electrode is at a pulse high potential, two processes mainly occur (one is electromigration and the other is the formation of organic SEI). Specifically, first, the electrode interface has a higher capacitance and combines more lithium ions, so that a strong electric field is generated in the double layer region. Under the action of the electric field, the anions accumulate at the electrode interface, and electromigration occurs. Secondly, the solvation structure in the electrolyte begins to decompose at this potential. As a result of the decomposition, not only organic SEI components are formed on the electrode surface, but also a large number of free solvent molecules are released. (2) When the electrode is at a pulse low potential, two processes (diffusion and the formation of inorganic SEI) also occur. Specifically, first, due to the enrichment of a large number of solvent molecules on the electrode surface, a large diffusion potential is formed, and the solvent molecules move to the side away from the electrode under the action of diffusion. Secondly, since anionic groups are enriched on the electrode surface at high potential, the conditions for reduction reaction are met at this time, and electrons are obtained from the electrode interface to undergo decomposition reaction, thereby forming inorganic SEI components derived from anions (such as LiF) on the electrode surface. (3) The setting of the high and low potential of the pulse is to adjust the competitiveness of the decomposition of anions and solvent molecules, and also the competitiveness of the formation of inorganic components and organic components. Therefore, the setting of the pulse protocol determines the SEI components. If the high potential duration is prolonged, it is conducive to the migration of anions to the electrode surface, and more organic SEI components will be formed. In the quantitative analysis, the results are shown as Pulse (30:1). If the low potential duration of the pulse is prolonged, it is conducive to the diffusion of free solvent molecules, and more inorganic SEI components will be formed. In the quantitative analysis, the results are shown as Pulse (1:30). When the high and low potential durations of the pulse are equal, the inorganic SEI components are relatively more and the performance is better. In the quantitative analysis, the results are shown as Pulse (1:1).

[0068] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0069] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0070] Example 1

[0071] 0.1 g of silicon nanoparticles (particle size 60-100 nm) were uniformly dispersed in 10 mL of anhydrous ethanol and ultrasonicated for 30 min using an ultrasonic disperser until a uniform ethanol suspension was formed.

[0072] 20 μL of the ethanol suspension was evenly applied three times on a copper foam with a diameter of 1.2 cm and a thickness of 0.6 mm by drop coating. The copper foam after drop coating was dried in a vacuum drying oven at 80°C for 5 h, and then placed in a powder tablet press, and a pressure of 30 MPa was applied and maintained for 60 s to obtain a silicon anode without a binder or a conductive agent (wherein the loading amount of silicon nanoparticles on the silicon anode was 0.9 mg / cm 2 );

[0073] The silicon anode obtained above was assembled into a CR2032 button cell, wherein the counter electrode was a metal lithium sheet with a diameter of 16 mm, the electrolyte was 1 M LiPF6 + (EC / DEC = 1:1) + 10% FEC, and the battery case was CR2032 + 15.8 mm * 1.0 mm gasket + 15.4 mm * 1.2 mm funnel shrapnel;

[0074] The assembled CR2032 button cells were subjected to pulse voltage pretreatment using an IviumStat2.h electrochemical workstation as a pulse signal generator. The parameters of the pulse voltage treatment (abbreviated as Pulse (1:1)) are shown in Table 1.

[0075] Table 1 Parameters of pulse voltage treatment

[0076] parameter symbol illustrate unit Pulse high potential <![CDATA[H v ]]> Apply pulsed high potential 1.2V Pulse high potential time <![CDATA[H t ]]> High potential duration 1ms Pulse low potential [[ L v ]]> Apply pulsed low potential 0.1V Pulse low potential time <![CDATA[L t ]]> Low potential duration 1ms Pulse duration t The duration of the entire pulse treatment 10s

[0077] Example 2

[0078] The assembled CR2032 button battery was subjected to pulse voltage treatment in the manner of Example 1, wherein the parameters of the pulse voltage (abbreviated as: Pulse (30:1)) are shown in Table 2;

[0079] Table 2 Parameters of pulse voltage treatment

[0080] parameter symbol illustrate unit Pulse high potential <![CDATA[H v ]]> Apply pulsed high potential 1.2V Pulse high potential time <![CDATA[H t ]]> High potential duration 30ms Pulse low potential <![CDATA[L v ]]> Apply pulsed low potential 0.1V Pulse low potential time [[ L t ]]> Low potential duration 1ms Pulse duration t The duration of the entire pulse treatment 10s

[0081] Example 3

[0082] The assembled CR2032 button battery was subjected to pulse voltage treatment in the manner of Example 1, wherein the parameters of the pulse voltage (abbreviated as: Pulse (1:30)) are shown in Table 3;

[0083] Table 3 Parameters of pulse voltage treatment

[0084] parameter symbol illustrate unit Pulse high potential <![CDATA[H v ]]> Apply pulsed high potential 1.2V Pulse high potential time <![CDATA[H t ]]> High potential duration 1ms Pulse low potential <![CDATA[L v ]]> Apply pulsed low potential 0.1V Pulse low potential time <![CDATA[L t ]]> Low voltage duration 30ms Pulse duration t The duration of the entire pulse treatment 10s

[0085] Example 4

[0086] The assembled CR2032 button battery was subjected to pulse voltage treatment in the manner of Example 1, wherein the parameters of the pulse voltage (abbreviated as: Pulse (1:1)) are shown in Table 4;

[0087] Table 4 Parameters of pulse voltage treatment

[0088] parameter symbol illustrate unit Pulse high potential <![CDATA[H v ]]> Apply pulsed high potential 1.2V Pulse high potential time <![CDATA[H t ]]> High potential duration 1ms Pulse low potential [[ L v ]]> Apply pulsed low potential 0.1V Pulse low potential time <![CDATA[L t ]]> Low voltage duration 1ms Pulse duration t The duration of the entire pulse treatment 1s, 2s, 4s, 6s, 10s

[0089] The battery after pulse voltage treatment is tested for AC impedance spectrum. The test results are as follows: Figure 12 As shown in the figure, it can be seen that with the extension of the pulse voltage treatment time, R_SEI gradually decreases within 6s (from 147Ω to 72Ω) and gradually reaches stability within 8 to 10s.

[0090] Example 5

[0091] The assembled CR2032 button cells were subjected to pulse voltage treatment in the manner of Example 1, wherein the electrolyte was 1M LiTFSI in THF; an untreated CR2032 button cell was used as a blank control (i.e. Figure 13 In the subsequent tests, the CR2032 button batteries used as blank controls were all new batteries.

[0092] The AC impedance spectrum of the battery after pulse voltage treatment and the blank control was tested. The test results are as follows: Figure 13 As shown, it can be seen that the EIS test shows an impedance value of 73Ω when there is no treatment (and blank control). After the pulse (1:1) treatment, the impedance is reduced to 38Ω. The pulse voltage treatment method can also be applied to 1M LiTFSI THF electrolyte.

[0093] Performance Testing

[0094] Test Example 1

[0095] 1. The battery treated with pulse voltage in Example 1 was disassembled and the silicon anode therein was characterized.

[0096] (1) Figure 1 The first row from left to right are the TEM overall morphology of SEI formed on silicon anode and the HRTEM detailed morphology of SEI formed on silicon anode. The second row from left to right are the element analysis selected area morphology of SEI on silicon anode surface and the element distribution map of SEI on silicon anode surface. Figure 1It can be seen that TEM shows that a layer of SEI layer about 10nm thick is attached to the surface of the silicon anode nanoparticles after pulse treatment. The SEI components are mainly composed of C, O, F, and P. In the HRTEM image, a low-crystallinity organic layer is observed on the surface of the silicon particles, tightly attached to the crystalline Si. Inside the organic layer, a large number of highly crystalline inorganic SEI small particles with a lattice spacing of 0.19nm are evenly dispersed, which is very close to the lattice spacing of LiF(200).

[0097] (2) Figure 2 From top to bottom are the XRD patterns and Raman patterns of silicon anode. Figure 2 It can be seen that in the in-situ XRD, the bulge between 20 and 24 degrees corresponds to amorphous SiO2. After the silicon anode is pretreated with pulse voltage, the bulge of silicon dioxide is significantly reduced. The peak at 35.6 degrees corresponds to the lithium product of silicon Li x Si, after the pulse voltage treatment, the peak increases significantly. This shows that when the pulse voltage is applied to the fresh battery, the extension of the pulse low potential duration is conducive to the lithiation of the surface SiO2, and the lithiation product is converted into Li x Si. In situ Raman shows that after pulse voltage pretreatment, the silicon peaks are significantly reduced. This is because the SEI layer covers the original silicon surface, reducing the signal value. -1 EC-Li + With 717 and 894cm -1 The free / uncoordinated EC band signal shows a significant increase in intensity, which is attributed to the fact that extending the duration of the high-potential pulse is beneficial to the EC-Li + and free / unliganded EC migrates to the vicinity of the EDL.

[0098] (3) Figure 3 The middle ones are the deep etching curves of Li, Si, C, O, and F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, the depth distribution curves of the relative content of each element drawn from the deep etching curves of Li, Si, C, O, and F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, the deep etching analysis diagram of C1s and F1s fine spectrum of the SEI on the surface of the silicon anode after pulse treatment, the deep etching analysis diagram of the relative content of PF, CF, and Li-F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, and the deep etching analysis diagram of the relative content of CC, CO, C=O, Li2CO3, and OCF of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment.

[0099] from Figure 3It can be seen that high-resolution XPS spectral analysis and elemental composition analysis during the XPS etching process show that when the Pulse (1:1) pulse protocol is applied, it has a higher F (17%) and Li (15%) content. Specifically, a unique peak at 684.5eV in the F1s spectrum is assigned to the Li-F bond, revealing that the SEI layer formed on the surface of the silicon anode contains inorganic components of LiF. The content of LiF in each etched layer is about 7% to 8%. In the C1s spectrum, four different CC, CO, C=O and OCF components are displayed at 284.8, 286.4, 288.4 and 291.5eV, corresponding to alkane components, alkyl lithium carbonate (ROCO2Li) and Li2CO3, respectively. They are typical products of the SEI layer formed by the decomposition of carbonate solvents, indicating the formation of an SEI layer.

[0100] 2. Perform performance tests on the pulse voltage treated batteries.

[0101] The untreated CR2032 button cell was used as a blank control (i.e. Figure 4 Without pulse in ).

[0102] Figure 4 From top to bottom in the middle are the EIS impedance analysis graphs of the blank control and the battery after pulse treatment, the CV comparison curves of the original silicon anode (i.e., blank control) and after pulse treatment, and the voltage-to-capacity curves of the original silicon anode and the first week after pulse treatment.

[0103] The EIS impedance of the silicon anode significantly decreased after pulse (1:1) treatment. The EIS graph shows that the battery's impedance was 384Ω in the initial state, but decreased to 98Ω after pulse (1:1) treatment, representing a 74.47% reduction. In the CV test curve, the original silicon anode exhibited a distinct cathode peak at around 1.2V in the first cycle, while the pulse-treated silicon anode exhibited no significant cathode peak in the first cycle. The original silicon anode had an ICE of 85.4%, while the pulse-treated silicon anode achieved an ICE of 90.8%. The original silicon anode had a discharge capacity of 2409.64mAh / g, while the pulse-treated silicon anode achieved a discharge capacity of 2666.66mAh / g.

[0104] 3. The CR2032 button battery assembled in the manner of Example 1 was subjected to pulse (1:1) treatment in the manner of Example 1 and then to formation treatment; the specific formation treatment process was as follows: the button battery was discharged at a constant current density of 100 mA / g to 0.1 V (referred to as sample PC) using a Xinwei CT-40008 channel battery tester.

[0105] The impedance of the batteries obtained by three treatment methods (i.e. original silicon anode, after pulse treatment, and after pulse + formation treatment) was tested respectively. Figure 16 The following are the EIS impedance analysis diagrams of the batteries after three treatment methods and the TEM images of the silicon anode after formation.

[0106] Figure 16 It can be seen that the EIS test of the original silicon anode shows an impedance value of 367Ω. After the Pulse (1:1) treatment, the impedance is reduced to 98Ω (the impedance reduction rate is 73.29%). After the conventional formation (constant current discharge to 0.1V), the impedance is 117Ω. Figure 16 The TEM shows that after pulse-formation (first treated with Pulse (1:1) and then discharged at a constant current to 0.1V), the thickness of SEI is (10-15nm) and there are obvious small crystal particles.

[0107] Figure 17 They are the deep etching curves of Li, Si, C, O, and F of SEI on the surface of sample PC by high-resolution XPS, the relative content depth distribution curves of each element made from the deep etching curves of Li, Si, C, O, and F of SEI on the surface of sample PC by high-resolution XPS, and the deep etching analysis diagrams of C1s and F1s fine spectra of SEI on the surface of sample PC by high-resolution XPS; Figure 17 It can be seen that deep etching XPS shows that after pulse formation (first treated with Pulse (1:1) and then discharged at a constant current of 0.1V), the relative content of F element in SEI is 20-22%, and the relative content of carbon element is 13-14%.

[0108] Test Example 2

[0109] Referring to the method of Test Example 1, performance tests were performed on the silicon anode and battery after pulse voltage treatment in Example 2.

[0110] (1) Figure 5 The middle ones are the deep etching curves of Li, Si, C, O, and F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, the depth distribution curves of the relative content of each element drawn from the deep etching curves of Li, Si, C, O, and F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, the deep etching analysis diagram of C1s and F1s fine spectrum of the SEI on the surface of the silicon anode after pulse treatment, the deep etching analysis diagram of the relative content of PF, CF, and Li-F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, and the deep etching analysis diagram of the relative content of CC, CO, C=O, Li2CO3, and OCF of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment.

[0111] from Figure 5 High-resolution XPS spectral analysis and elemental composition analysis during the XPS etching process indicate that, when the Pulse (30:1) protocol was applied, the F (8%) and Li (8%) contents were lower than those in Example 1. Specifically, a unique peak at 684.5 eV in the F1s spectrum was assigned to the Li-F bond, revealing that the SEI layer formed on the silicon anode surface contained an inorganic component called LiF, with the LiF content in each etched layer being 4%. The higher intensity of the CO peak in the C1s spectrum indicates a higher content of the organic component ROCO2Li in the SEI layer.

[0112] (2) Figure 6 From left to right in the figure are the EIS impedance analysis graphs of the battery after pulse treatment and blank control, the original silicon anode (i.e. blank control, not pulse treated) and the voltage-to-capacity curve in the first week after pulse treatment. It can be seen that the EIS impedance of the silicon anode is significantly reduced after Pulse (30:1) pulse treatment. The EIS graph shows that the impedance of the original silicon anode is 384Ω. After pulse Pulse (30:1) treatment, the impedance of the battery is reduced to 192Ω, and the impedance reduction rate is 50%; the ICE of the original silicon anode is 85.4%, and the ICE of the silicon anode after Pulse (30:1) pulse treatment reaches 86.85%. The discharge specific capacity of the original silicon anode is 2409.64mAh / g, and the discharge specific capacity of the silicon anode after Pulse (30:1) pulse treatment reaches 2406.62mAh / g.

[0113] Test Example 3

[0114] Referring to the method of Test Example 1, performance tests were performed on the silicon anode and battery after pulse voltage treatment in Example 3.

[0115] (1) Figure 7 The middle ones are the deep etching curves of Li, Si, C, O, and F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, the depth distribution curves of the relative content of each element drawn from the deep etching curves of Li, Si, C, O, and F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, the deep etching analysis diagram of C1s and F1s fine spectrum of the SEI on the surface of the silicon anode after pulse treatment, the deep etching analysis diagram of the relative content of PF, CF, and Li-F of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment, and the deep etching analysis diagram of the relative content of CC, CO, C=O, Li2CO3, and OCF of the high-resolution XPS of the SEI on the surface of the silicon anode after pulse treatment.

[0116] from Figure 7It can be seen that high-resolution XPS spectral analysis and elemental composition analysis during the XPS etching process show that when the Pulse (1:30) pulse protocol is applied, the F (14%) and Li (14%) contents are lower than those in Example 1. Specifically, a unique peak at 684.5 eV in the F1s spectrum is assigned to the Li-F bond, revealing that the SEI layer formed on the silicon anode surface contains inorganic components such as LiF. The LiF content in each etched layer is 5% to 7%. In the C1s spectrum, a unique peak at 290.3 eV is assigned to Li2CO3, which has a higher content of 7% to 8% in each etched layer.

[0117] (2) Figure 8 From left to right, the EIS impedance analysis graphs for the battery after pulse treatment and a blank control, and the voltage-to-capacity curves for the original silicon anode (i.e., without pulse treatment) and the first week after pulse treatment, show that the EIS impedance of the silicon anode significantly decreased after pulse (1:30) treatment. The EIS graph shows that the impedance of the original silicon anode was 412Ω, and after pulse (1:1) treatment, the impedance of the battery decreased to 112Ω, a reduction rate of 72.81%. The ICE of the original silicon anode was 85.4%, and the ICE of the silicon anode after pulse (1:30) treatment reached 88.09%. The discharge capacity of the original silicon anode was 2409.64mAh / g, and the discharge capacity of the silicon anode after pulse (30:1) treatment reached 2690.36mAh / g.

[0118] Comparative Example 1

[0119] The assembled CR2032 button battery was subjected to pulse voltage treatment in the manner of Example 1, wherein the parameters of the pulse voltage (abbreviated as: Pulse (60:1)) are shown in Table 5;

[0120] Table 5 Parameters of pulse voltage treatment

[0121] parameter symbol illustrate unit Pulse high potential <![CDATA[H v ]]> Apply pulsed high potential 1.2V Pulse high potential time <![CDATA[H t ]]> High potential duration 60ms Pulse low potential <![CDATA[L v ]]> Apply pulsed low potential 0.1V Pulse low potential time <![CDATA[L t ]]> Low voltage duration 1ms Pulse duration t The duration of the entire pulse treatment 10s

[0122] The battery after pulse voltage treatment is tested for AC impedance spectrum. The test results are as follows: Figure 10 As shown, it can be seen that the EIS test shows that the silicon anode impedance value is 312Ω when there is no treatment (i.e., blank control). After the Pulse (60:1) treatment, the impedance is reduced to 162Ω, and the impedance reduction rate is 48.07%. The silicon anode impedance is significantly reduced after the pulse voltage treatment. Compared with Example 1, increasing the pulse high potential duration to 60ms also helps to form the SEI layer on the silicon anode surface, but the impedance reduction rate is significantly lower than that of Example 1.

[0123] Comparative Example 2

[0124] The assembled CR2032 button cell was subjected to pulse voltage treatment in the manner of Example 1, wherein the parameters of the pulse voltage (referred to as: Pulse (1:60)) are shown in Table 6;

[0125] Table 6 Parameters of pulse voltage treatment

[0126] parameter symbol illustrate unit Pulse high potential <![CDATA[H v ]]> Apply pulsed high potential 1.2V Pulse high potential time <![CDATA[H t ]]> High potential duration 1ms Pulse low potential <![CDATA[L v ]]> Apply pulsed low potential 0.1V Pulse low potential time <![CDATA[L t ]]> Low potential duration 60ms Pulse duration t The duration of the entire pulse treatment 10s

[0127] The battery after pulse voltage treatment was subjected to AC impedance spectrum test, and the test results are shown in Figure 11 It can be seen that the EIS test shows that the impedance value of the silicon anode is 255Ω without treatment, and the impedance is reduced to 174.5Ω after Pulse (60:1) treatment, and the impedance reduction rate is 31.57%; the impedance of the silicon anode after Pulse (1:60) pulse voltage treatment is significantly reduced. Compared with Comparative Example 1, the increase of the pulse low potential duration to 60ms also helps to form SEI layer on the surface of the silicon anode, but the impedance reduction rate is obviously lower than that of Example 1.

[0128] Comparative Example 3

[0129] The CR2032 button cell obtained in Example 1 was taken as a sample and subjected to conventional formation treatment.

[0130] The specific formation process was as follows: the button cell was discharged at a current density of 100 mA / g to 0.1 V by a new CT-40008 channel battery tester (referred to as sample C).

[0131] Figure 14 The EIS impedance analysis diagram and TEM diagram of sample C are shown in

[0132] It can be seen from Figure 14 that the EIS test shows that the impedance value is 300Ω without treatment, and the impedance is reduced to 148Ω after conventional formation (constant current discharge to 0.1V). Figure 14 The TEM shows that the thickness of SEI is (20-25nm) after conventional formation (constant current discharge to 0.1V), and there is no obvious small crystal particle.

[0133] Figure 15 The high-resolution XPS depth etching curve diagram of Li, Si, C, O and F of the surface SEI of sample C, the relative content depth distribution curve diagram of each element made by the depth etching curve of Li, Si, C, O and F of the high-resolution XPS of the surface SEI of sample C, and the C1s, F1s fine spectrum depth etching analysis diagram of the high-resolution XPS of the surface SEI of sample C are shown in Figure 15Deep etching XPS shows that after conventional formation (constant current discharge to 0.1 V), the relative content of F element in SEI is 8-10%, and the relative content of carbon element is 16-19%.

[0134] Although the above embodiment provides a detailed description of the present invention, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A method for forming an SEI film on the surface of a silicon anode, characterized in that: The following steps are involved: Providing a device comprising a silicon anode, a counter electrode, and a lithium-ion battery electrolyte, wherein the silicon anode and the counter electrode are immersed in the lithium-ion battery electrolyte; The device is subjected to a pulse voltage treatment to form a SEI film on the surface of the silicon anode.

2. The method according to claim 1, characterized in that The conditions of the pulse voltage treatment include: pulse high potential of 0.7-1.2V, pulse high potential time of 1-30ms, pulse low potential of -0.5-0.1V, pulse low potential time of 1-30ms, and pulse voltage treatment duration of 1-60s.

3. The method according to claim 2, characterized in that The conditions of the pulse voltage treatment include: a pulse high potential of 1.2 V, a pulse high potential time of 1 ms, a pulse low potential of 0.1 V, a pulse low potential time of 1 ms, and a duration of the pulse voltage treatment of 10 s.

4. The method according to claim 2, characterized in that The conditions of the pulse voltage treatment include: a pulse high potential of 1.2 V, a pulse high potential time of 30 ms, a pulse low potential of 0.1 V, a pulse low potential time of 1 ms, and a duration of the pulse voltage treatment of 10 s.

5. The method according to claim 2, characterized in that The conditions of the pulse voltage treatment include: a pulse high potential of 1.2 V, a pulse high potential time of 1 ms, a pulse low potential of 0.1 V, a pulse low potential time of 30 ms, and a duration of the pulse voltage treatment of 10 s.

6. The method according to claim 1, characterized in that The silicon anode includes a current collector and elemental silicon located on the surface of the current collector; The thickness of the silicon anode is 30 to 50 μm, and the loading amount of the elemental silicon on the silicon anode is 0.6 to 1.8 mg / cm 2 ; The current collector includes copper foil or foam copper; the thickness of the copper foil is 6 to 20 μm, and the thickness of the foam copper is 0.5 to 1.5 mm.

7. The method according to claim 1 or 6, characterized in that The method for preparing the silicon anode comprises the following steps: dispersing silicon nanoparticles in ethanol to obtain an ethanol suspension; The ethanol suspension is drop-coated on a current collector, and then dried and pressed in sequence to obtain the silicon anode.

8. The method according to claim 7, characterized in that The particle size of the silicon nanoparticles is 60 to 120 nm; the dosage ratio of the silicon nanoparticles to ethanol is 0.1 to 1 g: 8 to 12 mL; The ratio of the ethanol suspension to the diameter of the current collector is 10-30 μL:1.2 cm; The pressing pressure is 30-40 MPa and the pressing time is 30-60 s.

9. The method according to claim 1, characterized in that The lithium-ion battery electrolyte includes LiPF6 electrolyte or LiTFSI electrolyte.

10. The method according to claim 1 or 9, characterized in that The device is a lithium ion half-cell; the counter electrode of the lithium ion half-cell is a metal lithium sheet.

Citation Information

Cited By

  • High-efficiency short-period lithium iron phosphate-graphite battery pulse formation method and lithium iron phosphate-graphite battery prepared by using same

    CN122202584A